Ingestion of anthropogenic debris by migratory barnacle geese Branta leucopsis on a remote north-eastern Atlantic island. (November 2020) - Coughlan, Neil E.; Doyle, Susan; Baker-Arney, Connie; Griffith, Rose M.; Lyne, Linda; Williams, Hannah; Kelly, Thomas C.; McMahon, Barry J.; Dick, Jaimie T.A.; Cunningham, Eoghan M.
Abstract: Although seabirds are frequently used as sentinel species for anthropogenic pollution, the extent and impacts of synthetic debris ingestion remains poorly studied for many water bird species. Here, we assess ingestion of synthetic particles (≥0.5 mm) by barnacle geese, Branta leucopsis, wintering on a remote island. Faecal samples were collected over a period of four wintering seasons. In total, 71 individual samples were assessed, with 79% of samples displaying at least one debris particle (maximum lengths 0.5–5 mm) from anthropogenic sources. The recovered synthetic debris were identified as micro-fibres ( n  = 166) and micro-fragments ( n  = 165). The number of synthetic particles detected per sample was generally low at 4.7 ± 0.9, 43 (mean ± SE, maximum): micro-fibres 2.3 ± 0.3, 10; micro-fragments 2.3 ± 0.8, 40. Particle numbers detected per gram of faecal sample differed amongst wintering seasons. Our results suggest that non-marine water birds can frequently ingest low quantities of synthetic particles in remote coastal habitats. Highlights: Synthetic micro-fibres and micro-fragments were recovered from bird faecal samples. Synthetic micro-debris (length: 0.5–5 mm) were detected in 78.9% of samples. Debris per gram of sample differed amongst years, months and wintering seasons. Ingestion of synthetic debris by B. leucopsis has been recorded for the first time. Non-marine birds can frequently ingest synthetic debris at a remote coastal site.